Electromagnetic Nondestructive Evaluation (XVI). - Rebello, J. M. A. (IOS Press, 2013)
Electromagnetic Nondestructive Evaluation (ENDE) is the process of inducing electric currents, magnetic fields or both within a test object to assess its condition by observing the electromagnetic response. An important tool in fields as diverse as engineering, medicine and art, it does not permanently alter the object being tested, thus proving invaluable for product evaluation, troubleshooting and research. This book presents the proceedings of the 17th International Workshop on Electromagnetic Nondestructive Evaluation (ENDE), held in Rio de Janeiro, Brazil, in July 2012. ENDE workshop is a.